Pemanfaatan MYOB Premier V.16 Dalam Membantu Pengolahan Data Akuntansi - Lala Nilawati; Wulan Oktaviani (LPPM Universitas Bina Sarana Informatika, 2021)
The development of increasingly sophisticated technology as it is today can support success in various fields. One of them is the existence of an accounting application that can be used in carrying out the company's business activities, which functions as a medium for processing company accounting data. Mustika Buana Karya Depok shop has not used computer assistance at all or has not been computerized, in the process of processing financial data. Processing of accounting data that is still done manually can allow for errors, such as loss of transaction documents that arise due to the many transactions that occur every day, and are still considered not in accordance with existing accounting data processing standards. A computerized system can be a solution for Mustika Buana Karya Depok Shop, to minimize errors in processing accounting data. MYOB Premier V. 16 can be an alternative that is expected to help overcome the problems that are currently happening, so that the processing of accounting data at the Mustika Buana Karya Depok store can run more effectively and efficiently compared to manual data processing.